2018
DOI: 10.1002/jpen.1492
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Index Is a Simple Objective Screening Tool for Malnutrition in the Critically Ill

Abstract: Background Reliable and valid tools to screen for malnutrition in the intensive care unit (ICU) remain elusive. The sarcopenia index (SI) [(serum creatinine/serum cystatin C) × 100], could be an inexpensive, objective tool to predict malnutrition. We evaluated the SI as a screening tool for malnutrition in the ICU and compared it with the modified‐NUTRIC score. Materials and Methods This was a historical cohort study of ICU patients with stable kidney function admitted to Mayo Clinic ICUs between 2008 and 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 31 publications
1
38
0
3
Order By: Relevance
“…In a retrospective study conducted in adult ICU patients, the SI was related to in-hospital and 90-day mortality 16 . Recently, another retrospective study also found that a lower SI was associated with a significantly higher risk of mortality among adult ICU patients 27 . Our finding that the SI was associated with long-term mortality among hospitalized older patients was in line with these findings.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In a retrospective study conducted in adult ICU patients, the SI was related to in-hospital and 90-day mortality 16 . Recently, another retrospective study also found that a lower SI was associated with a significantly higher risk of mortality among adult ICU patients 27 . Our finding that the SI was associated with long-term mortality among hospitalized older patients was in line with these findings.…”
Section: Discussionmentioning
confidence: 95%
“…As we aforementioned, due to the defects of current diagnostic methods for sarcopenia, the validation of a specific biomarker as the surrogate marker of sarcopenia is an attractive method 25 . As a newcomer in this field, the SI and a very similar biomarker (serum creatinine/cystatin C ratio) are of low cost, high accessibility, and repeatability 26 , therefore, they have been studied in different populations since being introduced in 2015 [16][17][18][19]27 . Only two previous studies addressed the association between the SI and mortality 16,27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vallejo y colaboradores reportaron que 74 % (n = 745/1053) de estos pacientes presentaban malnutrición de moderada a severa según la Evaluación Global Subjetiva (11) . Esta proporción es significativamente alta comparada con la observada (30 % -50 %) en estudios Norteamericanos y Europeos (12)(13)(14) . Dado que pacientes con deficiencias nutricionales preexistentes se pueden beneficiar más del apoyo nutricional artificial (15) , la literatura actual impide extender las recomendaciones actuales de prescripción de proteína al contexto latinoamericano debido a la falta de datos disponibles resultado de estudios procedentes de esta zona.…”
Section: Opiniónunclassified